Clinical characteristics and high risk factors of patients with Omicron variant strain infection in Hebei, China - Wang, Lihong; Liu, Ting; Yue, Hongjuan; Zhang, Jiaojiao; Sheng, Qihong; Wu, Ling; Wang, Xiaoyu; Zhang, Mei; Wang, Jing; Wang, Jia; Yu, Weifang (Frontiers in Cellular and Infection Microbiology, 2023)
Objective The Omicron variant has a weaker pathogenicity compared to the Delta variant but is highly transmissible and elderly critically ill patients account for the majority. This study has significant implications for guiding clinical personalized treatment and effectively utilizing healthcare resources. Methods The study focuses on 157 patients infected with the novel coronavirus Omicron variant, from December, 2022, to February, 2023. The objective is to analyze the baseline data, test results, imaging findings and identify risk factors associated with severe illness. Results Among the 157 included patients, there were 55 cases in the non-severe group (all were moderate cases) and 102 cases in the severe group (including severe and critical cases). Infection with the Omicron variant exhibits significant differences between non-severe and severe cases (baseline data, blood routine, coagulation, inflammatory markers, cardiac, liver, kidney functions, Chest CT, VTE score, etc.). A multifactorial logistic regression analysis showed that neutrophil percentage >75%, eosinophil percentage <0.4%, D-dimer >0.55 mg/L, PCT >0.25 ng/mL, LDH >250 U/L, albumin <40 g/L, A/G ratio <1.2, cholinesterase<5100 U/L, uric acid >357 mole/L and blood calcium<2.11 mmol/L were the most likely independent risk factors for severe novel coronavirus infection. Conclusion Advanced age, low oxygenation index, elevated neutrophil percentage, decreased eosinophil percentage, elevated PCT, elevated LDH, decreased albumin, decreased A/G ratio, elevated uric acid, decreased blood calcium, and elevated D-dimer are independent prognostic risk factors for non-severe patients progressing to severe illness. These factors should be closely monitored and actively treated to prevent or minimize the occurrence of severe illness.